Pembuatan Lawung Sumping Berbahan Kulit Kayu Nyamu di Prodi Pendidikan Luar Sekolah (PLS) Universitas Palangka Raya: The Creation of Lawung Sumping Made from Nyamu Bark in the Non-Formal Education Program at the University of Palangka Raya - Triyadi, Antonius; Tanduh, Yusintha; Joni, Herwin; Toni, Hendra; Rosdiana, Rosdiana (HUTAN TROPIKA, 2024)
Non-Timber Forest Products, such as Nyamu/Breadfruit Bark (Artocarpus altilis), are utilized by the Dayak community as the primary material for making traditional attire. Complementary items like Sumping and Lawung are also crafted. In the past, these Lawung and Sumping were simple, with minimal ornamentation or accessories. However, as demand has grown, decorations such as sequins, beads, and embroidery have been added. Despite these enhancements, the designs still reflect the distinctive characteristics of the Dayak tribe in Central Kalimantan. The challenges faced by the partners involved in this initiative include Partners have no prior experience in making Lawung and Sumping, although these products are in high demand; As educators in the Non-Formal Education program, the partners feel it is crucial to provide entrepreneurial skills to their students; and Partners need to understand the techniques for applying accessories such as sequins, beads, embroidery, and bird feathers to enhance the aesthetic appeal of bark-based materials. The primary challenge that needs immediate attention is transferring knowledge to enhance participants' skills so they can create job opportunities, design innovative and attractive crafts, and produce high-quality products that align with market demands. The use of simple and reliable technology is introduced to participants, emphasizing that bark can be transformed into desirable products instead of being wasted. This results in unique, distinctive, and beautiful items. Implementing sewing machines and techniques for embellishing bark materials with sequins is a straightforward technological application accessible to all participants. The training benefits education by incorporating aspects of local wisdom into the curriculum for both formal and non-formal education. By introducing regional crafts, participants can explore creativity, innovation, and entrepreneurial opportunities. The products created include Lawung and Sumping with motifs inspired by Bajakah (a traditional plant) and birds, adorned with embroidery, sequins, and bird feathers for the Sumping.